PERSEPSI MAHASISWA CALON GURU MATEMATIKA TERHADAP PENGGUNAAN ALAT PERAGA MANIPULATIF - Afit Istiandaru; Vita Istihapsari (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2017)
The effective use of manipulatives still become a debate among the mathematics educatos. This research aims to describe the perception of pre-service teacher towards the use of manipulatives in mathematics teaching practice. This research is a qualitative research which focused on the students’ responses of mathematics education department towards the aspect of effectiveness of manipulatives, the aspect of students, the aspect of material, and the aspect of learning strategy through the administration of questionnaire and interview. The research subjects were also involved in developing the manipulative project and used them in a peer teaching session. The result suggested that 83.3% of respondents believed that manipulatives could effectively help students to understand the mathematics concept. There were 50% respondents believed that all students, regardless their level of understanding ability, need a manipulatives-aided learning. However, it was only 20,8% who thought that all mathematics material can be taught using manipulatives and 62,5% thought that teacher needs a special strategy to implement the manipulatives in their learning. The perception reflects that it is still important to develop manipulatives in mathematics learning.